Renal nephroprotection during chemotherapy with platinum compounds in cancer patients - Szczylik, Cezary; Wcisło, Gabriel; Bodnar, Lubomir; Miedzińska-Maciejewska, Magdalena (Contemporary Oncology/Współczesna Onkologia, 2003)
Kidneys are responsible for the excretion of some chemical substances including cytotoxic agents. Cisplatin and its analogs are considered to have a nephrotoxicity profile that renders acute or chronic renal insufficiency. The main purpose of our article is to show how cisplatin and its analogs are harmful to kidneys. We are focusing on magnesium homeostasis disturbances after cisplatin therapy. Nevertheless, we presented methods of renal protection through a magnesium supplementation made intravenously and its oral continuation. From the clinical point of view, renal functions are measured through creatinine clearance which is influenced by many unpredicted factors and, therefore, shows its clinical limitations. Hence there is a great need to establish very sensitive factors that would help to detect early nephrotoxicity. Some proteins are suspected to be helpful such as beta-2-microglobulin, N-acetyl-beta-D-gluconidase (NAG), alaninaminopeptidase (AAP), glutamyltranspherase, leucine aminopeptidase, alpha-glutation-S-transpherase, and cystatin C. As shown oxaliplatin is a new cisplatin analog that is not nephrotoxic. Despite progress in chemotherapy there is a limited number of nephroprotective chemicals as simple as magnesium, and more complex chemicals like: amifostine or BNP7787. We do hope that our article clarifies the knowledge of cisplatin analogs as one of the most popular drugs used in oncology with respect to kidneys. This theme is of clinical interest because renal toxicity may stop a proper therapy that gives unsuccessful results.